Dr - F N MacDickson Celt (My University, 2025)
This review critically examines the proposed multicenter clinical trial designed to evaluate a novel palm-sized, battery-operated electrochemical biosensor for rapid detection of infectious disease biomarkers. The analysis covers the project’s rationale, objectives, device description, trial methodology, partnerships, regulatory framework, anticipated impact, key strengths, potential challenges, and recommendations for optimization.